Food Toxicology: Theory, Practice and Resolve in Vietnam - Huy, Ba Le; Xuan, Hoan Nguyen; Tan, Phong Nguyen; Minh , Thanh Le (Food Toxicology: Theory, Practice and Resolve in Vietnam, 2022)
The purpose and contents of this book are: 1- Clarification of the theory of articulation of the theory of Food Toxicology; 2- The current status of “Food Toxicoloy” in Vietnam (including rural and urban areas), so that scientists, administrators and the public know their current “food toxicology” as well as some developing countries development like Vietnam, where is it, how to have a solution; and 3-Technical and non-technical solutions to reduce and avoid exposure to toxic substances (Chemical toxic), toxins (Bio toxin). Obviously: The road from "mouth to the cemetery" is getting shorter and shorter, never as short as now.